Enhanced dissolution and bioavailability of grapefruit flavonoid Naringenin by solid dispersion utilizing fourth generation carrier. (26th March 2014) - Khan, Abdul Wadood; Kotta, Sabna; Ansari, Shahid Husain; Sharma, Rakesh Kumar; Ali, Javed
Abstract: Context : Naringenin (NRG), the aglycone flavonoid present in grapefruits, possesses anti-inflammatory, anti-carcinogenic, anti-lipid peroxidation and hepato-protective effects. However, it is poorly soluble in water and exhibits slow dissolution after oral ingestion, thus restricting its therapeutic efficacy. Objective : With the aim to enhance the dissolution rate and oral bioavailability of NRG, solid dispersion technique has been applied using Soluplus® as carrier. Methods : Solid dispersions of NRG were prepared by solvent evaporation and kneading methods using various ratios (1:4, 3:7, 2:3 and 1:1) of NRG:Carrier. Characterization of the optimized formulations was performed using Fourier transform infrared spectroscopy, differential scanning calorimetry (DSC) and X-ray diffraction (XRD) analysis. The in vivo behavior of the optimized formulations was also investigated in Wistar Albino rats. Results : NRG solid dispersion showed a significantly higher solubility and drug dissolution rate than pure NRG ( p < 0.001) and it followed the Higuchi model. Among the different methods employed for the preparation of solid dispersions, solvent evaporation showed better drug release profile. DSC analysis indicated reduced crystallinity of NRG as no discrete peaks of NRG were observed. This was further substantiated by XRD analysis. Furthermore, area under the drug concentration time-curve (AUC) of NRG from solid dispersion revealed a significant increase in NRG absorption compared to NRG alone. Conclusion : Based on these results, it was concluded that solid dispersion technique markedly enhances the in vitro drug release and in vivo behavior of the grapefruit flavonoid NRG.